Anomalous Pancreaticobiliary Ductal Union in Tropical Calcific Pancreatitis - Khuroo, Naira Sultan; Khuroo, Mohammad Sultan; Khuroo, Mehnaaz Sultan (JOP. Journal of the Pancreas, 2016)
Context Tropical calcific pancreatitis is unique to developing countries with of unknown origin. Objective We evaluated the pattern of pancreaticobiliary ductal union in patients with tropical calcific pancreatitis. Patients Twenty-one patients with tropical calcific pancreatitis were compared to 174 control subjects with no pancreaticobiliary disease and 35 patients with alcohol-induced chronic pancreatitis. Main outcome measure Two experienced people, blinded to the results, evaluated the pattern of pancreaticobiliary ductal union. Pancreaticobiliary ductal unions were classified as: separate ducts (no union), a short common-channel (length less than 6 mm), a long common-channel (length ranging 6-15 mm) and anomalous pancreaticobiliary ductal union (length greater than 15 mm). Anomalous union was defined as P-B type when the pancreatic duct appeared to join the bile duct and B-P type when the bile duct appeared to join the pancreatic duct. Any disparities between the two investigators were sorted out by mutual discussion. Results Pancreaticobiliary ductal union in tropical calcific pancreatitis patients as compared to those in the control group was as follows: separate ducts, 23.8% vs. 49.4% (P=0.036); a short common-channel, 4.8% vs. 28.7% (P=0.017); a long common channel, 33.3% vs. 18.4% (P=0.144) and anomalous pancreaticobiliary ductal union, 38.1% vs. 3.4% (P<0.001). The B-P pattern of anomalous pancreaticobiliary ductal union was more frequent in tropical calcific pancreatitis than in the control group but there was no statistical significance (P=0.103). The angle of the pancreaticobiliary ductal union in the tropical calcific pancreatitis group was 88.1±36.2° as compared to 20.0±11.5° in control group (P<0.001). Alcohol-induced chronic pancreatitis (No. 35) predominantly had either separate ducts (65.7%) or a short common channel (25.7%). Conclusion We concluded that patients with tropical calcific pancreatitis in Kashmir had anomalous pancreaticobiliary ductal union, predominantly of B-P type with a wide angle of ductal union more frequently. This may be related to the etiology of tropical calcific pancreatitis in such regions. Image: Large hepatic cystic lesions communicating with the bile ducts.